Экспериментальная оценка интервала фиксации пространственного весового вектора при последовательной пространственно-временной обработке сигналов на фоне комбинированных помех - Рябуха, В. П.; Рачков, Д. С.; Семеняка, А. В. (ХНУРЭ, 2011)
We consider separate space-time adaptive signal processing against the background of combined interferences, which involves the fixation of weight vector of spatial signal processing against the background of noise interferences for the time of adaptive interperiod signal processing against the background of clutter. By means of mathematical and hydroacoustic modeling the fixation interval is estimated, which keeps in allowable limits the losses in quality of noise interferences suppression.
Keywords: комбинированные помехи; источник шумовых излучений